Lymphocyte Subsets and Cytokine Changes in Women With Gestational Diabetes Mellitus: A Systematic Review - Wang Yu; Huang Miao; Yunhui Gong (Journal of Diabetes Research)
Conclusion: According to the results, there were no significant changes in CD3+ T cells, B cells, NK cells, IL-10, and IL-2 in GDM. However, the levels of IL-6 and TNF-α were higher or similar in GDM compared to non-GDM. The changes of other lymphocyte subsets and cytokines in GDM remained unclear.